Youth Aspirations for Integration of Old Serbia into Influential Social and Cultural Circles of Europe before the Balkan Wars - Stanojević, Saša D. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
This paper deals with the engagement of Serbian youth in social change placed in the context of critical historical events related to time before liberation of the area of Old Serbia in the Balkan Wars. Based on the testimony of some contemporaries and selected historiographical literature, article presents an analysis of the youth activities of the late 19th and especially at the beginning of the 20th century, which indicates its distinct and specific contribution to the cultural emancipation. A characteristic of the new era, with the idea of ​​national liberation, it’s a growing openness to European culture. In such a way, the primary military and political objective which is engaged Serbian youth naturally found in the same plane with the efforts of the Serbian government, an important task related and redirect these areas from lethargy of the archaic Ottoman Empire to modern European social and cultural sphere of influence. The ultimate self-sacrificing youth, guided by the most sincere convictions, was the element that is the fulfillment of the various activities of this national mission given particular impulse.